Knowledge, attitude and practice on chronic kidney disease progression prevention and readiness of mobile health application usage among early stages of chronic kidney disease patients at Island Hospital, Penang - Chieh, Lim Chia (2025)
Chronic kidney disease (CKD) is a significant health concern globally. Thus, early detection and treatment of kidney problems can prevent the kidney from deteriorating and causing complications, especially in Stages 1 and 2. Therefore, it is essential to access the patient’s knowledge, attitude and practice (KAP) to slow down the progression of the disease and to increase the mobile health application technology, which has been identified as one of the productive tools to aid patient care. This study aims to validate the mobile health application version questionnaire, determine the level of KAP, the readiness of mobile health applications (mHealth apps; Readiness of mHeatlh Applications RMHA) and the factors associated with it among early-stage CKD patients and who were patients from the nephrology clinic at Island Hospital. This study consisted of 2 phases. The respondents were early-stage CKD patients. For Phase 1, 200 respondents participated in the questionnaire validation for the Malay version of RMHA. The instrument used for the RMHA was the mHealth apps Malay version that originally in english version by (Putu et al., 2021). The data was analyzed by using SPSS 27 and Mplus8.0. The mean age of participants was 51.71 (SD=14.05), and the majority were male (57.5%). The Malay version of RMHA was valid and reliable based on confirmatory factor analysis and internal consistency reliability (Cronbach’s alpha ranged from 0.866 to 0.968). For Phase 2, 169 respondents completed the questionnaires to measure the KAP level and the readiness to use the mHealth apps. A cross-sectional study was conducted in Phase 2 and the researcher used convenience sampling to select eligible respondents for this study. The data were collected through KAP questionnaires. The data was analyzed by using SPSS 27 and Mplus8.0. From the linear regression analysis, factors that were found to be associated with mHealth readiness were gender (p=< 0.001), knowledge (p=0.027), technological readiness (p=< 0.001), people readiness (p=< 0.001), engagement readiness (p=< 0.001), and motivational readiness (p=< 0.001). The findings suggested that the early-stage CKD patients had good knowledge and attitude but poor practice on CKD. For the RMHA people, engagement and motivational readiness positively relate to mHealth readiness. The instrument used to screen KAP on CKD was the CKD Screening Index by Khalil (2014). The mean age of participants was 53.18 (SD=15.39), and the majority were male (51.4%). For KAP, the majority of the respondents have a high level of knowledge, n=270 (75.2%), a high level of attitude, n=331 (92.2%) but a low level of practice, n=228 (63.5%). The study concluded that early-stage CKD patients had good knowledge and attitude but poor practice, with technological and people readiness positively related to mHealth readiness.